SERUM IGE LEVEL IN MICE INFECTED WITH SINGLE DOSES OF ANCYLOSTOMA CANINUM LARVAE - VARDHANI, V. VIVEKA; G. SAKUNTHALA, (The Bioscan, 2014)
The level of IgE in the serum of singly infected mice (group A, 500 dose; B, 1000 dose; group C, 2000 dose) was studied during murine ancylostomiasis in all the 3 groups of singly infected animals, IgE level began to decrease on 1st day of infection, reached the lowest value on day 30 and progressively declined from day 1 to 30 of experimental period. Statistical analysis indicated a significant decrease in all the 3 groups when compared with controls. These studies demonstrated that the larval antigens provoked an immune response resulting into a low level of serum IgE in the mouse system.